Modern experimental methods for assessing the effectiveness of tissue-engineered products for hyaline cartilage regeneration - Bozhokin, M. S.; Korneva, Yu. S.; Bozhkova, S. A.; Mikhaylova, E. R.; Marchenko, D. M.; Rakhimov, B. R.; Nashchekina, Y. A.; Khotin, M. G. (Frontiers in Bioengineering and Biotechnology, 2025)
Hyaline cartilage (HC) is a specialized connective tissue that covers the surfaces of major joints and is characterized by its limited regenerative capacity. Modern therapeutic approaches to HC restoration often do not provide complete regeneration of damaged tissue. Developed tissue engineering methods show promise as effective approaches for restoring various types of HC damage. Due to the rapid evolution of various technologies in research practice, the range of methods available for analysis of TE constructs has expanded, including for the study of tissue engineering of hyaline cartilage (TEHC). Because of the complexity of the HC’s structure, a whole range of methods is needed to assess characteristics of the scaffold, such as structure and strength. It is also important to study the behavior of cells inside the TE construct at all stages of cultivation, including post transplantation into the damaged area. The opacity of the scaffold and the complexity of its architecture often cause issues with the cell visualization and assessment of their viability. Therefore, there is a need to optimize each specific method for each specific scaffold. Despite the active study of TEHC, the results remain unsatisfactory. In this study, we have systematized data on the effectiveness and feasibility of methods to analyze structure, mechanical characteristics, cell interaction with the scaffold, and their ability to form new tissue before and after transplantation.